2006
DOI: 10.1111/j.1365-2249.2006.03162.x
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of Beijing family genotypes ofMycobacterium tuberculosisand low-level protection by bacille Calmette–Guérin (BCG) vaccines: is there a link?

Abstract: SummaryThe world is confronted with major tuberculosis (TB) outbreaks at a time when the protection of bacillus Calmette-Guérin (BCG) vaccine has become inconsistent and controversial. Major

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 86 publications
(116 reference statements)
4
76
0
Order By: Relevance
“…Although the modern and ancient Beijing strains seem to be closely related on the genetic level (30), differences in association with (multi)drug resistance and in the ability to cause and spread disease (31) have been described between both sublineages. Moreover, after several studies suggested enhanced ability of Beijing strains in general to circumvent BCG-vaccine induced immunity (13,14), one study reported that modern Beijing strains were isolated more frequently from BCG-vaccinated patients than nonvaccinated individuals (9). The observation that the interaction of modern Beijing strains with the immune system is different than that of ancient strains was further confirmed by a recent study that described differences in pro-inflammatory cytokine induction for both strains (32).…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Although the modern and ancient Beijing strains seem to be closely related on the genetic level (30), differences in association with (multi)drug resistance and in the ability to cause and spread disease (31) have been described between both sublineages. Moreover, after several studies suggested enhanced ability of Beijing strains in general to circumvent BCG-vaccine induced immunity (13,14), one study reported that modern Beijing strains were isolated more frequently from BCG-vaccinated patients than nonvaccinated individuals (9). The observation that the interaction of modern Beijing strains with the immune system is different than that of ancient strains was further confirmed by a recent study that described differences in pro-inflammatory cytokine induction for both strains (32).…”
supporting
confidence: 53%
“…However, multiple studies have shown that modern Beijing strains are more "successful" in terms of transmission and development of antibiotic resistance (13,14,31,65,66). Moreover, in most geographic areas with a higher density of Beijing strains the modern Beijing strain are predominant, except for Japan (28).…”
Section: Selection Of M Tuberculosis Beijing Genotypementioning
confidence: 99%
“…This could be a plausible explanation, and the fact that in this study we showed that, within the most prevalent strain families, particular genotypes predominated lends further support to this assumption. This finding warrants further evaluation, using animal models, of the ability of the predominant ST50 and ST42 genotypes to circumvent BCG vaccination as previously shown for Beijing strains (Lopez et al, 2003;Abebe & Bjune, 2006). Moreover, consanguinity and endogamy, which can reach 50 % in certain Tunisian areas (Ben Arab et al, 2004;Riou et al, 1989), may have contributed to the accommodation of particular M. tuberculosis genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The factors contributing to the adaptability of M. tuberculosis strains or lineages to a particular population are poorly understood and several may be involved. Among these, selective pressure imposed by Bacille Calmette-Guérin (BCG) vaccination could have played an important role (Abebe & Bjune, 2006;Gagneux et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They are thought to have emerged from China where BCG vaccination has been implemented for almost two decades and that this vaccination favored their selection, resisting BCG-induced immunity [72]. Beijing strains are also found to demonstrate distinct expression patterns of proteins; several species of α-crystallin (a known M. tuberculosis virulence factor) are enhanced, while there is decreased expression of heat shock protein of 65 kDa and many others [72]. In addition, the Beijing family strains produce high levels of phenolic glycolipid (PGL-tb), not made by H37Rv.…”
Section: Genetics Of Natural Populations Of M Tuberculosismentioning
confidence: 99%